Komparasi Pendapatan dan Kelayakan Usahatani Padi Sawah Tadah Hujan Kabupaten Barru - Arifin, Arifin; La Sumange, La Sumange; Azisah, Azisah; Sadat, Mohammad Anwar; Pata, Abdul Asis; Biba, Muhammad Arsyad (Universitas Galuh, 2024)
Income aims to describe the state of ongoing agricultural activities and to describe the conditions of plans or actions in the future. A high feasibility ratio is expected to increase the income level of farmers. The survival of agriculture is a measure to state that the business is feasible in the sense that it can provide and generate profits. The purpose of this study was to analyze the comparative income and feasibility of rainfed lowland rice farming. Data collection techniques used are observation/observation, interviews, and documentation. The data analysis method used is quantitative descriptive analysis for income and feasibility. The results showed that the average income in Barru District was IDR 4,803,663.33. While the average income in Tanete Riaja District is IDR 7,042,598.06. Based on the results of the t-test analysis, there is a difference and a significant effect with an error rate of 1% in terms of income. Barru District (Sape'e and Coppo Villages) obtained an R/C ratio value of 1.94. It can be interpreted that each expenditure costs IDR 1.00 then you will get an income of IDR 1.94. Meanwhile, Tanete Riaja Subdistrict (Lompo Tengah and Lempang Villages) obtained an R/C ratio value of 2.20. This means that each expenditure costs IDR 1.00 then you will get an income of IDR 2,20. With the results of the feasibility value obtained from rainfed lowland rice farming in Barru District (Sape'e and Coppo Villages) and Tanete Riaja District (Lompo Tengah and Lempang Villages) Barru Regency, it is feasible to cultivate. The income from rainfed lowland rice farming in Tanete Riaja District (Lompo Tengah and Lempang Villages) is greater than Barru District (Sape'e and Coppo Villages) Barru Regency. Tanete Riaja Subdistrict (Lompo Tengah and Lempang Villages) has greater eligibility than Barru District (Sape'e and Coppo Villages).